Identification of pathogenic fungi causing leaf spot of Urtica cannabina and Malus sieversii in the wild fruit forest of Tianshan Mountain, Xinjiang, China - Tang, Jieshi; Liu, Yu; Zhang, Chi; Han, Caixia; Shao, Hua (Penerbit Universiti Kebangsaan Malaysia, 2022)
Degradation of the wild apple trees in the wild fruit forest of Tianshan mountain of Xinjiang Province, China, has attracted great attention in recent years, and pathogens are believed to be an important responsible factor. We observed that Malus sieversii and its understory plant, Urtica cannabina, exhibited similar symptoms of leaf spot disease, and we suspect that they are caused by the same pathogens. DNA sequencing using ITS1 and ITS4 primers was applied to identify the pathogenic fungi from diseased leaves of U. cannabina and M. sieversii, which led to the identification of Alternaria sp. and Fusarium sp. as active pathogens causing same symptoms on leaves of both species. Our results implied that these two plants shared the same pathogenic fungi that cause leaf spot disease, and infection of the understory species U. cannabina might provide a reservoir of the pathogens which can attack M. sieversii and contribute at least in part, to the degradation of M. sieversii.